Urgensi Kualitas Wirakoperasi dan Kompetensi Pengurus terhadap Kinerja Koperasi - Indra Fahmi (LPPM Universitas Koperasi Indonesia, 2025)
This study aims to examine the urgency of cooperative entrepreneurial qualities and management competencies in influencing cooperative performance in Indonesia through a qualitative literature study approach. Cooperative entrepreneurship, as a form of internalizing the entrepreneurial spirit within the framework of cooperative values, encompasses a positive mental attitude, innovation, courage to take risks, and commitment to cooperative principles. Meanwhile, management competencies encompass cooperative knowledge, managerial skills, and integrity, which serve as the foundation for professional and sustainable cooperative management. A review of primary literature sources, including academic journals, textbooks, and policy reports, indicates that cooperatives with management possessing high cooperative entrepreneurial qualities and adequate competencies tend to demonstrate better organizational performance. This performance is reflected in healthy liquidity ratios, stable asset growth, and increased levels of independent capital. These findings confirm that strengthening human resources, particularly at the management level, is a key prerequisite for cooperative institutional transformation. Therefore, capacity building strategies such as integrated training, management certification, and needs-based coaching are strategic steps that need to be prioritized in national cooperative development policies.